Psychosocial work environment and mental health among the global workforce of seafarers in the wake of the COVID-19 pandemic - Rebecca Hayes-Mejia; Martin Stafström (BMC, 2023)
Abstract Background The aim of this study was to investigate the impact of the COVID-19 pandemic on the mental health outcomes of international seafarers, who played a crucial role in maintaining global trade during the pandemic. The study examined how changes in psychosocial work environment and policies affected mental health outcomes among seafarers. Methods We analyzed a survey including answers from 17,861 seafarers, serving on 44 different international commercial vessels with 154 different nationalities. Stress, anxiety, and depression were applied as outcome measures in this study. Three sets of independent variables were included; work-related consequences of the COVID-19 pandemic, general psychosocial work environment onboard, and socioeconomic variables. First, we applied binary linear regression, followed by a multivariate linear regression analysis. Results The study found that changes in safety consciousness and clear communication from employers were associated with better mental health outcomes among seafarers. Eroded policies related to crew changes had a significant negative effect on mental wellbeing due to delays caused by national quarantine guidelines and travel restrictions. The results also showed a discrepancy in mental health outcomes between those onboard and those onshore, with stress being present in both groups. Conclusions The findings suggest that crisis management within shipping companies played an important role in mitigating adverse mental health outcomes during the pandemic. Clear communication from employers and emphasizing safety issues onboard were effective strategies for promoting better mental wellbeing among seafarers. However, delays in crew changes had a significant negative impact on mental health outcomes, highlighting the need for global cooperation and overarching agreements to protect international seafarers during times of crises.